The authority of lawyers - Heike Jung (Oñati Socio-Legal Series, 2012)
The public standing of lawyers has always been somewhat ambivalent. On the one hand, they have been taken for a conceited technocratical elite with their own incomprehensible language. On the other hand, they have been cherished as the number one trouble-shooter and peace-maker. Today, the traditional monopoly of lawyers has come under pressure. Rivaling professions such as mediators want to have their share of the conflict resolution market. Still, lawyers are likely to retain the greater bulk.